The Impact of Diet on the Involvement of Non-Coding RNAs, Extracellular Vesicles, and Gut Microbiome-Virome in Colorectal Cancer Initiation and Progression - Ekine-Afolabi, Bene A.; Njan, Anoka A.; Rotimi, Solomon O.; R. I., Anu; Elbehi, Attia M.; Cash, Elizabeth; Adeyeye, Ademola (Frontiers in Oncology, 2020)
Cancer is the major cause of morbidity and mortality in the world today. The third most common cancer and which is most diet related is colorectal cancer (CRC). Although there is complexity and limited understanding in the link between diet and CRC, the advancement in research methods have demonstrated the involvement of non-coding RNAs (ncRNAs) as key regulators of gene expression. MicroRNAs (miRNAs) which are a class of ncRNAs are key players in cancer related pathways in the context of dietary modulation. The involvement of ncRNA in cancer progression has recently been clarified throughout the last decade. ncRNAs are involved in biological processes relating to tumor onset and progression. The advances in research have given insights into cell to cell communication, by highlighting the pivotal involvement of extracellular vesicle (EV) associated-ncRNAs in tumorigenesis. The abundance and stability of EV associated ncRNAs act as a new diagnostic and therapeutic target for cancer. The understanding of the deranging of these molecules in cancer can give access to modulating the expression of the ncRNAs, thereby influencing the cancer phenotype. Food derived exosomes/vesicles (FDE) are gaining interest in the implication of exosomes in cell-cell communication with little or no understanding to date on the role FDE plays. There are resident microbiota in the colon; to which the imbalance in the normal intestinal occurrence leads to chronic inflammation and the production of carcinogenic metabolites that lead to neoplasm. Limited studies have shown the implication of various types of microbiome in CRC incidence, without particular emphasis on fungi and protozoa. This review discusses important dietary factors in relation to the expression of EV-associated ncRNAs in CRC, the impact of diet on the colon ecosystem with particular emphasis on molecular mechanisms of interactions in the ecosystem, the influence of homeostasis regulators such as glutathione, and its conjugating enzyme-glutathione S-transferase (GST) polymorphism on intestinal ecosystem, oxidative stress response, and its relationship to DNA adduct fighting enzyme-0-6-methylguanine-DNA methyltransferase. The understanding of the molecular mechanisms and interaction in the intestinal ecosystem will inform on the diagnostic, preventive and prognosis as well as treatment of CRC.